Artemídia impermanente: do transe ao trânsito de um editor de conteúdo de livros didáticos - Machado, Paulo Eduardo Ferreira [UNESP] (2015)
T his study aims at observing and interpreting the nature of a phenomenon:the content editing process of a textbook series on English as aforeign language. It proposes to accomplish the task by assuming that processes in content edition fid parallel in art practice processes. At fist, the investigation provides an overview of the researcher-artisteditor's quest for the study object itself, trying to indicate how this search is embedded in the editor's professional practice. On the other hand, the editing process is scrutinized from textualizations put down in a perspective of exotopy, based on the interactions of the editor with the other subjects in the process, on the researcher-artist-editor's pad notes and textual elements of the editing object, that is, the textbook series. These textualizations are the groundwork for interpretation from a hermeneutic phenomenological point of view, which tries to identify the themes underlying the phenomenon's nature. Once the emerging themes of the content editing process of a textbook series on English as a foreign language phenomenon are identifid, they are commented or re-textualized through images. These images are, on their side, result of the processes and proceedings carried out by the researcherartist-editor in his aesthetic quest. Thus, taking into consideration the concept ofserendipity, what at fist could be characterized in this research as the object of study, ended up, at last, as a tool for commenting and interpreting the themes that make up the nature of the editing process phenomenon.